2014
DOI: 10.4103/0019-509x.138303
|View full text |Cite
|
Sign up to set email alerts
|

Microbial colonization of Provox voice prosthesis in the Indian scenario

Abstract: Candida is the most common organism grown on voice prosthesis in Indian scenario. Consumption of curd and history of prior radiotherapy significantly affect Provox prosthesis lifespan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…There is a variety of data published about VP lifespan. Some authors assessed that the average time of Provox Vega exploitation ranges from 3.5–18 months [ 27 , 28 ]. The average and median number of replacements per year is smaller than in another study, where the results were an average of 2.2 replacements and a median of 4.1 replacements per year [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a variety of data published about VP lifespan. Some authors assessed that the average time of Provox Vega exploitation ranges from 3.5–18 months [ 27 , 28 ]. The average and median number of replacements per year is smaller than in another study, where the results were an average of 2.2 replacements and a median of 4.1 replacements per year [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Factors influencing the time of voice prosthesis degradation are primary or postoperative irradiation for the head and neck region, as well as diet. Some studies have proven that consuming large quantities of dairy products has a significant effect on the extension of VP exploitation time [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is however likely that differences in the identification methods used, different patient demographics or lifestyles and different lifestyles or dietary habits will impact upon the microbial colonization of VP. For instance, Chaturvedi et al (2014) found that C. tropicalis was the most prevalent fungal species colonizing VP within an Indian patient cohort. The high consumption of dairy products such as yogurt and buttermilk in India has been proposed to influence biofilm growth on VPs.…”
Section: Discussionmentioning
confidence: 99%